Physiological parameters related to oocyte nuclear differentiation for the improvement of IVM/IVF outcomes in women and cattle - Buratini, Jose [UNESP]; Soares, Ana Caroline Silva [UNESP]; Barros, Rodrigo Garcia; Dellaqua, Thaisy Tino [UNESP]; Lodde, Valentina; Franciosi, Federica; Dal Canto, Mariabeatrice; Renzini, Mario Mignini; Luciano, Alberto Maria (CSIRO Publishing, 2021)
In vitro maturation (IVM) has been applied in numerous different contexts and strategies in humans and animals, but in both cases it represents a challenge still far from being overcome. Despite the large dataset produced over the last two decades on the mechanisms that govern antral follicular development and oocyte metabolism and differentiation, IVM outcomes are still unsatisfactory. This review specifically focuses on data concerning the potential consequences of using supraphysiological levels of FSH during IVM, as well as on the regulation of oocyte chromatin dynamics and its utility as a potential marker of oocyte developmental competence. Taken together, the data revisited herein indicate that a significant improvement in IVM efficacy may be provided by the integration of pre-OPU patient-specific protocols preparing the oocyte population for IVM and more physiological culture systems mimicking more precisely the follicular environment that would be experienced by the recovered oocytes until completion of metaphase II.
Keywords: bovine; chromatin configuration; cumulus cells; FSH; germinal vesicle; human; in vitro maturation (IVM); oocyte